A case report of a rare ramification pattern and distribution area of the mesenteric arteries in a Japanese White rabbit (Oryctolagus cuniculus) - KIGATA, Tetsuhito (J Vet Med Sci, 2019)
The rabbit intestinal tract is supplied by the cranial and caudal mesenteric arteries. Generally, the cranial mesenteric artery supplies the duodenum, jejunum, ileum, cecum, proximal colon and ascending and transverse distal colon, whereas the caudal mesenteric artery supplies the descending distal colon and rectum. The present study describes an abnormal branching pattern of the cranial and caudal mesenteric arteries in a Japanese White rabbit, where the caudal mesenteric artery but not the cranial mesenteric artery supplied the distal ileum, cecum, proximal colon and ascending and transverse distal colon. Such a rare mesenteric arterial ramification pattern may be explained by anomalies of the remaining anastomotic branches between the primitive mesenteric arteries and regressed their parent arteries during the developmental process.